A facile fabrication of copper particle-decorated novel graphene flower composites for enhanced detecting of nitrite. Issue 4 (8th January 2015) - Wang, Huiwen; Wang, Caiqin; Yang, Beibei; Zhai, Chunyang; Bin, Duan; Zhang, Ke; Yang, Ping; Du, Yukou
Abstract : A novel 3D porous flower-like reduced graphene oxide (f-RGO) was explored as the support material for the Cu particles on glassy carbon electrode (Cu/f-RGO/GCE) for detecting nitrite. Abstract : We describe a simple electrochemical preparation method of a novel three dimensional (3D) graphene material, porous flower-like reduced graphene oxide (f-RGO) nanosheets, which was explored as the support for Cu particles on a glassy carbon electrode (Cu/f-RGO/GCE) for detecting nitrite. In morphology studies, scanning electron microscopy (SEM) demonstrates the 3D porous structure of f-RGO enlarges the surface area of the electrode and promotes more Cu particles depositing on the surface of f-RGO with homogeneous dispersion. In cyclic voltammetry (CV), a well-defined voltammetric peak along with the remarkable reduction current indicates excellent electrocatalytic activity of the Cu/f-RGO/GCE for NaNO2 reduction compared with other corresponding electrodes. The effects of pH value and detection potential on the current responses of Cu/f-RGO/GCE towards nitrite were optimized to obtain the maximal sensitivity. In the optimal experimental conditions, Cu/f-RGO/GCE displays the wide detection range from 0.15 μM to 10 500 μM and the low limit of detection of 0.06 μM (S/N = 3) with fast response time 2 s for detecting NaNO2 through an amperometric method. Furthermore, the presence of K +, Na +, Cl −, NH4 +, NO3 −, SO4 2− and ascorbic acid show a negligible effect on the current response of nitrite determination suggesting Cu/f-RGO/GCE have the high selectivity for detecting nitrite even in the presence of high concentration of interferents. Moreover, the real sample determination experiment indicated practical feasibility of the obtained sensor. The prepared sensor for determination of NaNO2 exhibited wide liner range, low detection limit, good reproducibility, nice stability and remarkable anti-interference ability. In this paper, not only did the Cu/f-RGO/GCE show high performance for determination of nitrite, but also it was simple to prepare, user-friendly and cost-effective.